Use of Enzymatic Bio-Fenton as a New Approach in Decolorization of Malachite Green - Afzal Karimi; Mostafa Aghbolaghy; Alireza Khataee; Shabnam Shoa Bargh (The Scientific World Journal)
An enzymatic reaction using glucose oxidase was applied for in situ production of hydrogen peroxide for use in simultaneously Fenton's reaction in decolorization of malachite green. It was found that decolorization rate increased by increasing of glucose concentration from 0.2 g/L to 1.5 g/L. Decolorization rate showed different behaviors versus temperature changes. Initial rate of decolorization process was increased by increasing of temperature; after 30 minutes, especially at temperatures above 30°C, the decolorization rate was gradually reduced. The pH value in the reaction media was decreased from natural to about pH=3 which had synergic effect on the Fenton process by stabilizing of Fe2+ ions.